Open questions about the farmlands’ biodiversity preservation in the cities’ peripheries – a Wrocław case (Poland) - Fudali, Ewa; Podlaska, Magda; koszelnik-Leszek, Anna; Szymanowski, Mariusz (Ecological Questions, 2023)
One of the necessary conditions for sustainable development is maintaining and developing environmental resources. The paper presents and discusses the idea that the field woods in the cities’ agricultural periphery, understood as habitats and not only a collection of trees, should be preserved and managed as a formal element of urban green infrastructure (GI). According to the authors, they should be seen as a great connecting element between urban green and the semi-natural areas outside. Even assuming the future land use transformation, it is worth preserving them from degradation just now. They play a role in protecting natural resources and the functions of ecosystems, expected from elements of GI, as they are a source of dispersion of various species of plants and animals benefit both for agricultural areas located further and for greenery in built-up areas. Using the authors’ own research on the farmland area situated within Wrocław administrative borders, and available literature, the following issues were considered: 1) the geographic and topographic characteristics of field woods, 2) evaluation of the role of field woods studied for the local biodiversity, 3) the risk factors for the degradation or disappearance of field woods and their biodiversity, 4) the legal regulations concerning the protection of field woods in Poland. Some legal and practical solutions are suggested.